2021
DOI: 10.1177/09603271211002884
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of N,N′-dimethylhydrazine induced colon toxicity by epigallocatechin gallate in Wistar rats

Abstract: Colon cancer is a life-threatening disease all over the world and is linked to constant oxidative stress and inflammation. Epigallocatechin gallate (EGCG), is a naturally occurring flavone possessing health benefiting pharmacological properties including antioxidant, anti-inflammatory and free radical scavenging properties. Our study investigates the role of EGCG on N,N′-dimethylhydrazine (DMH), a toxic environmental pollutant, induced colon toxicity. To investigate the effect of EGCG, Wistar rats were given E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Studies have also reported that in general, cancer and inflammation have reciprocal effects on each other. 31,58 In this regard, the anti-inflammatory effects of different parts of pomegranate fruit and its derivatives have been proven. 59,60 Thus, in this study, for the first time the effects of PFJ, PPE, and EA were investigated on altering the expression of some important inflammatory genes ( NF-κB, iNOS, IL-8, TNF-α ) in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that in general, cancer and inflammation have reciprocal effects on each other. 31,58 In this regard, the anti-inflammatory effects of different parts of pomegranate fruit and its derivatives have been proven. 59,60 Thus, in this study, for the first time the effects of PFJ, PPE, and EA were investigated on altering the expression of some important inflammatory genes ( NF-κB, iNOS, IL-8, TNF-α ) in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24,25 ] The control group received same volume saline. The EGCG group was administered with EGCG (20 mg/kg body weight per day) [ 26 ] dissolved in physiological saline by intraperitoneal injection. The EGCG + LPS group was administered with EGCG (20 mg/kg body weight per day) dissolved in physiological saline by intraperitoneal injection and then administered with 50 μl of LPS (1 mg/ml) by intrauterine perfusion.…”
Section: Methodsmentioning
confidence: 99%
“…EGCG can enhance the sensitivity of CRC cells to 5-FU chemotherapy through the NF-κB/miR-155-5p/MDR1 axis ( 13 ). According to previous animal models, EGCG inhibits N,N’-dimethylhydrazine-induced colon tumor development through its antioxidant and anti-inflammatory potential ( 10 , 14 ). In addition, EGCG can be used in combination with sodium butyrate to induce CRC cell cycle arrest and DNA damage ( 15 ).…”
Section: Nuclear Factor Kappa B Signaling Pathwaymentioning
confidence: 96%